Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content: 1. The spread of the phenomenon of atheism and ways to resist it Dr. Abdulhameed Abdo Mohsen Allaw 2. The relationships between Fatimah, the daughter of prophet Mohammed peace be upon him, and Abu Baker and Omar, may God be pleased with them all Dr. Hadi Qaed Alhabardi 3. Protecting family members from the inside according to Quranic middle approach Dr. Naif Nasser Almansour 4. Women’s Issues in Liberal Thought "The Verses of Inheritance as a Model" Mrs. Mona Saud Al-Mutairi 5. Sarfa as one of the miraculous aspects of The Quran between the supporters and opponents, review and study Dr. Shahd Atwan Saleh Al-Maliki